Pengaruh Promosi dan Fluktuasi Harga Emas terhadap Peningkatan Jumlah Nasabah pada Produk Murabahah Logam Mulia untuk Investasi Abadi (MULIA) di PT Pegadaian Cabang Cikudapateuh Kota Bandung - Gina Alamiah; Sakura Sakura; Widwi Handari Adji (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Precious Metals are one type of gold for a long-term investment with minimal risk. The goal of this research is to see how Promotions and Price Fluctuations affect Increasing the Number of Customers on Murabahah Precious Metal Products For Lasting Investment (MULIA) at PT Pegadaian Cikudapateuh branch in Bandung. This research uses the incidental sampling technique to obtain is 100 respondents. The quantitative implementing approach, descriptive, was used in the analytical method. Data collection using observation, literature studies, and questionnaires were analyzed using SPSS version 25 software, it is evident that promotional variables affect increasing the number of customers, while price fluctuations do not affect the increase in the number of customers partially. Simultaneously, promotions and price fluctuations affect the number of customers with a contribution value of 16,9% and the remaining 83,1% is influenced by other variables like the quality of the product, place, service quality, and brand image. Keywords: promotion, price fluctuations, increasing the number of customers